Morphology of sulphur-terminated compound deposits condensed on different substrates in vacuum - Grytsenko, K.P.; Lytvyn, P.M.; Doroshenko, T.P.; Kolomzarov, Yu.V.; Bricks, J.L.; Kurdyukov, V.V.; Slominskii, Yu.L.; Tolmachev, O.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Thin films of new sulphur-terminated organic compounds were deposited by evaporation in vacuum onto the glass, silicone, gold and polytetrafluoroethylene substrates. The influence of compound chemical structure and substrate type on morphology of the condensed solid was studied using atomic force microscopy. The significant difference in morphology of the same dye but deposited on various substrates was found.